Transponder Designs for Harmonic Radar Applications - Kimmo Rasilainen; Ville V. Viikari (International Journal of Antennas and Propagation)
This work presents a review on the concept of harmonic or secondary radar, where a tag or transponder is used to respond at a harmonic multiple of the incoming interrogation signal. In harmonic radar, the tag is called a harmonic transponder and the necessary frequency multiplication is implemented using a nonlinear element, such as a Schottky diode. Different applications and operating frequencies of harmonic transponders are presented, along with various tag design aspects. The designer may have to deal with certain tradeoffs during the design with respect to a number of transponder properties, and the role of these tradeoffs is also considered. Additionally, techniques usable for characterization of harmonic transponders are discussed.